The extracellular phage-host interactions involved in the bacteriophage LL-H infection of Lactobacillus delbrueckii ssp. lactis ATCC 15808 - Munsch-Alatossava, Patricia; Alatossava, Tapani (Frontiers in Microbiology, 2013)
The complete genome sequence of Lactobacillus bacteriophage LL-H was determined in 1996. Accordingly, LL-H has been used as a model phage for the infection of dairy Lactobacillus, specifically for thermophilic Lb. delbrueckii ssp. lactis host strains, such as ATCC 15808. One of the major goals of phage LL-H research consisted of the characterization of the the first phage-host interactions at the level of phage adsorption and phage DNA injection steps to determine effective and practical methods to minimise the risks associated with the appearance and attack of phages in the manufacture of yoghurt, and Swiss or Italian type hard cheeses, which typically use thermophilic LAB starter cultures containing Lb. delbrueckii strains among others. This mini review article summarises the present data concerning (i) the special features, particle structure and components of phage LL-H and (ii) the structure and properties of lipoteichoic acids (LTAs), which are the phage LL-H receptor components of Lb. delbrueckii ssp. lactis host strains. Moreover, a model of the first, extracellular, phage-host interactions for the infection of Lb. delbrueckii ssp. lactis ATCC 15808 by phage LL-H is presented and further discussed.